2012
DOI: 10.1083/jcb.201202058
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of CaMKII to dendritic microtubules supports the plasticity of local synapses

Abstract: Synaptic plasticity correlates with the local dendritic translocation of CaMKII in a Ca2+- and microtubule-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 68 publications
2
54
1
Order By: Relevance
“…Hanson et al (1994) predicted that repetitive calcium pulses would lead to the recruitment of limited calmodulin to the holoenzyme, which would further stimulate autophosphorylation while De Koninck et al (1998) showed that the enzyme can decode the frequency of Ca 2+ spikes into distinct amounts of kinase activity. Hence, a calcium increase compartmentalized in an activated spine would lead to CaMKII activation specifically in that subcellular region (Lee et al 2009;Lemieux et al 2012). On the other hand, calcium increases happening through voltage-dependent calcium channels or endoplasmic reticulum release might convey a specific signal supporting the plasticity of neighboring synapses (Greer and Greenberg 2008;Wheeler et al 2008;Rose et al 2009).…”
mentioning
confidence: 99%
“…Hanson et al (1994) predicted that repetitive calcium pulses would lead to the recruitment of limited calmodulin to the holoenzyme, which would further stimulate autophosphorylation while De Koninck et al (1998) showed that the enzyme can decode the frequency of Ca 2+ spikes into distinct amounts of kinase activity. Hence, a calcium increase compartmentalized in an activated spine would lead to CaMKII activation specifically in that subcellular region (Lee et al 2009;Lemieux et al 2012). On the other hand, calcium increases happening through voltage-dependent calcium channels or endoplasmic reticulum release might convey a specific signal supporting the plasticity of neighboring synapses (Greer and Greenberg 2008;Wheeler et al 2008;Rose et al 2009).…”
mentioning
confidence: 99%
“…This association and phosphorylation has even been proposed to be a means of directly encoding information on microtubules [33]. The only study of the functional consequences of the CaMKIIα/microtubule interaction [21] offered strong evidence that an interaction between CaMKIIα and dendritic microtubules increases the surface expression of AMPA receptors and spine remodelling. This study also showed that this translocation of CaMKIIα requires stable microtubules [21].…”
Section: Discussionmentioning
confidence: 99%
“…The only study of the functional consequences of the CaMKIIα/microtubule interaction [21] offered strong evidence that an interaction between CaMKIIα and dendritic microtubules increases the surface expression of AMPA receptors and spine remodelling. This study also showed that this translocation of CaMKIIα requires stable microtubules [21]. Although the intermediate mechanism is speculative, their result supports the model wherein activated CaMKIIα translocates to microtubules to ultimately potentiate synaptic strength.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas this question requires further investigation, it is interesting to note that CaMKIIa is a major player in the synaptic development and plasticity of both excitatory and inhibitory synapses. Indeed, CaMKIIa plays an essential role in decoding Ca 2+ signals in excitatory neurons and modulates the synaptic remodeling and plasticity of these cells [40][41][42][43]. CaMKIIa is also involved in the remodeling and plasticity of inhibitory synapses via trafficking of different GABA A receptor subunits as well as gephyrin, the main scaffolding protein of inhibitory synapses [44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%